Effect of boron incorporation on the bioactivity, structure, and mechanical properties of ordered mesoporous bioactive glasses. Issue 7 (29th January 2020) - Deilmann, Leonie; Winter, Oliver; Cerrutti, Bianca; Bradtmüller, Henrik; Herzig, Christopher; Limbeck, Andreas; Lahayne, Olaf; Hellmich, Christian; Eckert, Hellmut; Eder, Dominik
Abstract : B2 O3 doped (0.5–15 mol%) ordered mesoporous bioactive glasses were synthesized via sol–gel based evaporation-induced self-assembly using P123 as a structure directing agent and characterized by biokinetic, mechanical and structural investigations. Abstract : B2 O3 doped (0.5–15 mol%) ordered mesoporous bioactive glasses (MBG) with the composition 80% SiO2 –15% CaO–5% P2 O5 were synthesized via a sol–gel based evaporation-induced self-assembly process using the block-copolymer P123 as a structure directing agent and characterized by biokinetic, mechanical and structural investigations. Nitrogen physisorption isotherms and electron microscopy indicate no detrimental effect of B2 O3 on the ordered hexagonal pore structure. Boron incorporation increases both the bulk modulus and hardness of the glasses. In vitro bioactivity tests reveal a rapid initial release of Ca 2+ and PO4 3− ions, followed by formation of hydroxyapatite carbonate within a few hours. Contrary to the tight incorporation of Al in Al-doped MBGs, the rapid release of borate species into simulated-body-fluid suggests loosely bound species localized at the internal surfaces of the mesopores. 29 Si, 11 B, 31 P, and 1 H solid state NMR spectroscopy reveal that the majority of the borate is present as anionic BO4/2 − species. The need for charge compensation leads to an increase in the average degree of polymerization of the phosphate species for high boron contents. 11 B 31 P rotational echo double resonance NMR results reveal the absence of B–O–P linkages. This structural model explains the rapid release of borate and the enhanced dissolution kinetics of the Ca 2+ and phosphate species.